Ernst Troeltsch and Comparative Theology - Nix, Echol, Jr.; Nix, Echol, Jr. (Peter Lang, 2010)
Ernst Troeltsch and Comparative Theology examines the methodological attempts of Ernst Troeltsch and Robert Neville for discerning Christian normativity. The investigation of Troeltsch focuses on his treatment of the absoluteness of Christianity and highlights the crisis brought upon absolute religious claims by the study of the history of religions. By rejecting both the supernatural-exclusive apologetic of orthodox Protestantism and the evolutionary apologetic of liberal Protestantism, Troeltsch insists that theology$1 (Bs method should be the history of religions$1 (Bmethod (die religionsgeschichtliche Methode). Like Troeltsch, Neville agrees with historical inquiries, but, contrary to Troeltsch, Neville advances an axiological hypothesis to thinking, which is founded in valuation. Neville explains the role of valuation at the imaginative level of thinking and relates it to his theory of normative truth in religious symbols. This study shows that Neville begins with Troeltsch$1 (Bs methodological presuppositions but achieves more normative theology than Troeltsch, especially on ways in which God is engaged in symbolically shaped thinking and practice. Both thinkers offer creative insights for theology that make possible a critical comparison of truth claims regarding the validity of Christianity in and for a historically conscious age.s